Factors Related to Teachers' Perception of Problem Solving Skills Instruction - Tan, Ka Yu (1996)
This study aimed to: (1) ascertain the Form Two Integrated Living Skills (ILS) teachers' perception of problem solving skills instruction; (2) determine the relationships between the teachers' perception of problem solving skills instruction and teacher-related variables; and (3) determine the relationships between the teachers' perception of problem solving skills instruction and student-related variables. The teacher-related variables were demographic characteristics (i.e. gender, professional qualifications, teaching experience, in service courses attended and school location), and the teachers' perception of their own readiness for problem solving skills instruction. The student-related variables were the teachers' perception of student readiness for problem solving skills instruction, student mastery of the ILS contents and student intellectual capabilities. One hundred and fifty-five Form Two ILS secondary school teachers from the state of Negeri Sembilan served as respondents in the survey. A self administered questionnaire using a four-point Likert scale was used. Data were. analysed using descriptive statistics, correlational techniques and stepwise multiple regression. The findings showed that teachers indicated that they had infused problem solving skills into their current workshop instruction. Only two demographic variables, school locality and the number of lessons that the teachers taught in each week (a variable under teacher experience) had significant correlations with the teachers' perception of problem solving skills instruction. Positive and significant correlations were established between the overall teachers' perception of problem solving skills instruction and teacher readiness for the problem solving skills instruction, teachers' perception of student readiness for the problem solving skills instruction, and teachers' perception of student intellectual capabilities. Stepwise multiple regression analysis showed that teachers' perception of student intellectual capabilities, teacher readiness for problem solving skills instruction and number of ILS lessons taught each week accounted for 18 percent of the variance in the teachers' perception of problem solving skills instruction.